2001
DOI: 10.2527/2001.7961502x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postmortem storage on mu-calpain and m-calpain in ovine skeletal muscle.

Abstract: Casein zymography was used to determine the effect of postmortem storage on the proteolytic activity of mu-calpain and m-calpain in lamb longissimus. Casein zymography assays were conducted on crude muscle extracts (only one centrifugation). Six market weight crossbred lambs were slaughtered and a portion of the longissimus lumborum was removed at death (within 15 min of exsanguination) and after 3, 6, 9, 12, 24, 72, and 360 h postmortem. Muscle samples were snap-frozen in liquid nitrogen and stored at -70 deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
73
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 21 publications
11
73
2
Order By: Relevance
“…Note that at 4 μM CaCl 2 , the degraded calpain 1 is also active The native and the autolyzed forms have been shown to be active and bind tightly to intracellular structures such as myofibrils, where they proteolyze titin, nebulin, and desmin [31,36]. Native calpain 1 activity decreased faster than calpain 2 activity which is in agreement with the results in pig and lamb [32,45]. This is supported by Western blot analysis in bovine and ovine muscle, which demonstrated that the 80-kDa subunit of calpain 1 almost entirely degraded into a 76-kDa subunit within the first 7 days postmortem, while the 80-kDa subunit of calpain 2 remained undegraded in this period [42,46].…”
Section: Discussionsupporting
confidence: 87%
“…Note that at 4 μM CaCl 2 , the degraded calpain 1 is also active The native and the autolyzed forms have been shown to be active and bind tightly to intracellular structures such as myofibrils, where they proteolyze titin, nebulin, and desmin [31,36]. Native calpain 1 activity decreased faster than calpain 2 activity which is in agreement with the results in pig and lamb [32,45]. This is supported by Western blot analysis in bovine and ovine muscle, which demonstrated that the 80-kDa subunit of calpain 1 almost entirely degraded into a 76-kDa subunit within the first 7 days postmortem, while the 80-kDa subunit of calpain 2 remained undegraded in this period [42,46].…”
Section: Discussionsupporting
confidence: 87%
“…The myofibrillar samples were frozen at −80°C until used for assessing protein surface hydrophobicity and electrophoresis. Sarcoplasmic protein was prepared following the description of Veiseth et al (2001). All samples were homogenized with extraction solutions (10 mM ethylene diamine tetraacetic acid, 100 mM Tris-HCl, and 0.1 % β-mercaptoethanol (v/v), pH 8.3).…”
Section: Myofibrillar and Sarcoplasmic Protein Extractionmentioning
confidence: 99%
“…Protein extractions and immunoblots for the determination of AMPK phosphorylation were carried out on frozen liver and adipose tissue from mice according to a previous report (Shen et al, 2005). Briefl y, liver and adipose samples (0.1 g, 0.1 g, respectively) were powdered under liquid nitrogen and homogenized for 20 s in 500 μL buffer containing 20 mm Tris-HCl (pH 7.4 at 4°C), 2% SDS, 5 mm EDTA, 5 mm EGTA, 1 mm DTT, 100 mm NaF, 2 mm sodium vanadate, 0.5 mm phenylmethylsulfonyl fl uoride, 10 μg/mL leupeptin and 10 μL/ mL pepstatin (Raser et al, 1995;Veiseth et al, 2001). 40 μg of each homogenate was mixed with an equal amount of 2 × standard SDS sample loading buffer containing 125 mm Tris-HCl (pH 6.8), 4% SDS, 20% glycerol, 10% β-mercaptoethanol and 0.25% bromophenol blue, and boiled for 10 min before electrophoresis.…”
Section: Oral Glucose Tolerance Test (Ogtt)mentioning
confidence: 99%